Судьба украинского угля на фоне ситуации в Донбассе - Гринев, В.Г.; Калиущенко, Е.П. (Физико-технические проблемы горного производства, 2016)
Рассмотрены фактическая взаимосвязь в цепочках уголь-кокс-металл и уголь-электроэнергия на предприятиях Донбасса, а также в аналогичных цепочках с учетом оккупированных территорий. Проанализирована современная ситуация обеспечения угольной продукцией смежных с угледобывающей отраслей производства. Розглянуті фактичний взаємозв'язок в ланцюжках вугілля-кокс-метал і вугілля-електроенергія на підприємствах Донбасу, а також в аналогічних ланцюжках з урахуванням окупованих територій. Була проаналізована сучасна ситуація забезпечення вугільною продукцією суміжних з вуглевидобувною галузей виробництва. We have demonstrated that the Ukrainian coal industry has been falling into stagnation during two decades because of several reasons. The conception of the industry development was wrong and has not fostered modernization. Cheap raw materials shifted with deficiency of the coke and transition to high level prices, developed transportation infrastructure became wearied and inefficient, labor resources deficiency occurs, especially having high qualification, high degree of depreciation is typical for the fixed assets. Financial industrial groups have kept down coal prices and accumulated surplus profit in conjugated industries, namely energy production, metallurgy and machine building. Examination of the chains “coal – coke – metal” and “coal – energy” has demonstrated that, as a result of the war in Eastern Donbass, several components of these chains has been loosen including certain grades of coal, coal processing plants, coke and steel producers. We propose new strategy for Ukrainian coal industry development that should be based on integration of the energetic security and the market economy considering balance of all energetic resources and the industrial chains which include the coal. Presenting these chains as the mathematical graphs and considering as the networks, it is possible to optimize the production of metal energy and make it profitable. However all components of the chains (coal, coke, metal and energy) should be constituents of common financial and production structure.